MODERN METHODS OF RESEARCHING LANDSCAPES OF RIVER BASINS (Scientific journal of the Fergana State University, 2023)
This article is about delineating the basin of the Kosonsoy River on the basis of a digital elevation model, and creating a land use and land cover map of the basin using remote sensing and Geographic Information System (GIS).